Changes in muscle architecture and performance during a competitive season in female softball players - Nimphius, S.; McGuigan, M. R.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this research was (a) to examine the performance changes that occur in elite female softball players during 20 weeks of softball training (that included 14 weeks of periodized resistance training [RT]) and (b) to examine the relationship between percent change (%change) in muscle architecture variables and %change in strength, speed, and change of direction performance. Ten female softball players (age = 18.1 ± 1.6 years, height = 166.5 ± 8.9 cm, weight = 72.4 ± 10.8 kg) from a state Australian Institute of Sport softball team were tested for maximal lower-body strength using a 3 repetition maximum for a predicted 1 repetition maximum (1RM) and peak force, peak velocity (PV), and peak power (PP) were measured during jump squats (JS) unloaded and loaded. In addition, the first base (1B) and the second base (2B) sprint performance, change of direction (505) on dominant (D) and nondominant (ND) sides, aerobic capacity, and muscle architecture characteristics of vastus lateralis (VL) including muscle thickness (MT), fascicle length (FL), and pennation angle (?p) were examined. The testing sessions occurred pre, mid, and post training (total 20 week pre- and in-season training period). Changes over time were analyzed by repeated-measures analysis of variance. The relationship between %change in muscle architecture variables and strength, speed, and change of direction variables from pre to post were assessed by Pearson product-moment correlation coefficient. Significant improvements in PV and PP occurred at all JS loads pre- to mid-testing and pre- to post-testing. Significant increases occurred pre-post in absolute 1RM, relative 1RM, 505 ND, and 2B sprint. The strongest relationships were found between %change in VL MT and 1B sprint (r = -0.80, p = 0.06), %change in VL FL and 2B sprint (r = -0.835, p = 0.02), and %change in relative 1RM and 505 D (r = -0.70, p = 0.04). In conclusion, gains in strength, power, and performance can occur during the season in elite softball players who are also engaged in a periodized RT program. Furthermore, changes in performance measures are associated with changes in muscle architecture.